Does diminished ovarian reserve impact oxidation–reduction potential in follicular fluid? - Minh Tam Le; Nguyen Dac Nguyen; Hong Nhan Thi Dang; Quoc Huy Vu Nguyen (Journal of International Medical Research)
Objective This study aimed to evaluate oxidative stress in follicular fluid by measuring oxidation–reduction potential and determine its correlation with embryo quality in patients with diminished ovarian reserve. Methods This cross-sectional study included 134 patients with diminished ovarian reserve and 82 patients with normal ovarian reserve. Follicular fluid samples were collected from each patient via transvaginal aspiration under ultrasound guidance. Oxidation–reduction potential was measured using the Male Infertility Oxidative system, following the manufacturer’s protocol. Results The levels of anti-Müllerian hormone, number of oocytes retrieved, rate of blastocyst formation, and rate of high-quality embryos were significantly lower in the diminished ovarian reserve group than in the normal ovarian reserve group. Correlation analysis revealed that oxidation–reduction potential values had a negative correlation with the number of oocytes retrieved (r = −0.262, p = 0.002), rate of mature oocytes (r = −0.260, p = 0.002), and rate of normal fertilization (r = −0.207, p = 0.016); however, these values showed a positive correlation with the duration of ovarian stimulation (r = 0.186, p = 0.031). Conclusions Oxidative stress in follicular fluid correlates with a small number of oocytes retrieved, lower proportion of mature oocytes, and lower rate of normal fertilization in patients with diminished ovarian reserve.